The Contemporary Muslim between The Middle Ages and Modernity - Azad Raouf Qazaz (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2024)
This article delves into a crucial aspect of Islamic thought—the dynamic interplay between text and reality, with a particular focus on the Quranic text. It explores the implicit or explicit adherence to the idea that the fixed text, especially the Quran, holds supremacy over the ever-changing reality. The intricate relationship between text and reality has far-reaching implications for intellectual, scientific, and societal transformations throughout the history of human knowledge. This work aims to spotlight significant shifts and pivotal moments in human thought, driven by fundamental changes in how the relationship between text and reality is perceived. It argues that the accumulation of ideas from human experiences unlocks doors to unexplored realms that were previously overlooked. Here, "reality" refers to observable events and the revelations uncovered through human experiences, aligning closely with the concept of science. By the term "truth" here, I do not imply the existence of a predetermined entity that is lost to humans and needs to be discovered. No, the truth for us is the continuous discovery of the unknown. The article raises the question of when and how humanity shifted its focus from text to reality, giving rise to what is now known as the era of science, and it probes into the position of Muslims in this transformative period. This is a question that I attempt to answer. The author posits that the answer does not lie in the interpretation of religious texts, advocating for a broader perspective to unravel this inquiry. While contemporary Muslim thinkers seek answers through text interpretation. the author contends that the solution requires exploration from a different vantage point.